Economic analysis of microalgae biodiesel production in a small-scale facility. (December 2020) - Branco-Vieira, M.; Mata, T.M.; Martins, A.A.; Freitas, M.A.V.; Caetano, N.S.
Abstract: Industrial production and commercialization of biodiesel from microalgae have become a good alternative to conventional feedstock. Microalgae show high growth rate and carbon sequestration and can be easily cultivate in fresh and/or marine water, using non-arable soil. This study aims to analyze the technical and economic feasibility of biodiesel production from Phaeodactylum tricornutum, using an algae biomass production scaled-up scenario, considering local reality prices and available technologies. The model assumes 80, 000 m 3 of microalgae cultivation, in a set of bubble column photobioreactors installed on 15.247 ha of land, reaching a total of 1, 811 tons of microalgae biomass and 171, 705 L of biodiesel per year. The production cost estimated for microalgae biomass is 2.01 € kg −1 and for biodiesel is 0.33 € L −1 . The ROI calculated for the project is 10% with a 10 years' payback time and an EBITDA of 588, 139 € year −1 . Despite the project's viability in the medium term, the cost of producing microalgae biodiesel remains high when compared to fossil fuels. Thus, unless greater technological maturity is achieved to make the process more economical, it will not be viable in the short term.